Kegiatan Konferensi Pers dalam Meningkatkan Citra Kejaksaan Agung Republik Indonesia - Dea Agatha; Yugih Setyanto (Kiwari, 2023)
Press conferences are one of the government's public relations activities which are always held when there is important news information regarding the institution. Humas hopes journalists will show a neutral attitude and provide news that can form a positive image of the Indonesian Attorney General's office. This study discusses the influence of press conferences on the image of the Attorney General of the Republic of Indonesia. This study uses the theory of two-way asymmetrical and two-way symmetrical communication. Quantitative approach using survey method. Research data collected from questionnaires. Census sampling technique. Methods of data analysis using simple linear regression. The results of the influence of the press conference on the image of the Attorney General's Office of the Republic of Indonesia are in the strong category, which means that the more enhanced the press conference, the image of the Attorney General's Office of the Republic of Indonesia will increase, this is because the source conveying the communication message is a credible person, the content of the communication message is considered important, and the delivery the message is not very fast and easy to understand. Konferensi pers merupakan salah satu kegiatan humas pemerintah yang selalu diselanggarakan ketika ada informasi berita penting terkait institusinya. Humas berharap wartawan menunjukkan sikap netral dan menginformasikan berita yang dapat membentuk citra positif institusi Kejaksaan Agung RI. Penelitian membahas tentang pengaruh konferensi pers terhadap citra Kejaksaan Agung Republik Indonesia. Penelitian ini menggunakan teori two-way asymmetrical dan two-way symmetrical communication. Pendekatan kuantitatif menggunakan metode survei. Data penelitian dikumpulkan dari kuesioner. Teknik pengambilan sampel secara sensus. Metode analisis data menggunakan regresi linear sederhana. Hasil pengaruh konferensi pers terhadap citra Kejaksaan Agung Republik Indonesia termasuk kategori kuat, yang artinya semakin ditingkatkan konferensi pers maka akan semakin meningkat citra Kejaksaan Agung RI, hal ini dikarenakan narasumber yang menyampaikan pesan komunikasi merupakan orang yang kredibel, konten pesan komunikasinya dinilai penting, dan penyampaian pesannya tidak terlalu cepat dan mudah dimengerti.